Proceedings 2006 IEEE International Conference on Robotics and Automation, 2006. ICRA 2006.
DOI: 10.1109/robot.2006.1642233
|View full text |Cite
|
Sign up to set email alerts
|

System identification for the Berkeley lower extremity exoskeleton (BLEEX)

Abstract: The exoskeleton is an autonomous robotic device whose function is to increase the strength and endurance of a human pilot. In order to achieve an exoskeleton controller which reacts compliantly to external forces, an accurate model of the dynamics of the system is required. In this report, a series of system identification experiments are designed and carried out for the Berkeley Lower Extremity Exoskeleton. As well as determining the mass and inertia properties of the segments of the legs, various non-ideal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…Therefore, there were totally 46 sensors of various kinds incorporated in the system [14] . While this control strategy led to high sensitivity, its robustness tended to suffer, which rendered the system highly dependent upon active models, and which necessitated a large number of experiments to optimize all the parameters [15][16] . The BLEEX used a small diesel engine as power supply, and was packed a 4 L fuel tank [17] , because the team leader believed that hydrocarbon fuel was still the lightest energy source available.…”
Section: Active Exoskeletonsmentioning
confidence: 99%
“…Therefore, there were totally 46 sensors of various kinds incorporated in the system [14] . While this control strategy led to high sensitivity, its robustness tended to suffer, which rendered the system highly dependent upon active models, and which necessitated a large number of experiments to optimize all the parameters [15][16] . The BLEEX used a small diesel engine as power supply, and was packed a 4 L fuel tank [17] , because the team leader believed that hydrocarbon fuel was still the lightest energy source available.…”
Section: Active Exoskeletonsmentioning
confidence: 99%
“…Therefore, using the error between the identified torque and the measured torque to evaluate the identification accuracy is consistent with the original intention and application of exoskeleton parameter identification. The method of evaluating identification accuracy by the error between identified torque and measured torque has been verified and applied [21,32]. Ghan et al evaluated the identification accuracy by the agreement between the identified torque and measured torque [21].…”
Section: Quantitative Evaluation Methods For Identification Accuracymentioning
confidence: 99%
“…The method of evaluating identification accuracy by the error between identified torque and measured torque has been verified and applied [21,32]. Ghan et al evaluated the identification accuracy by the agreement between the identified torque and measured torque [21]. Bing et al used the comparison of identified torque and measured torque for evaluating the identification accuracy and comparing between PSO and LS.…”
Section: Quantitative Evaluation Methods For Identification Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…Recognition and Machine Intelligence Lab) PD PD 1 BLEEX [1][2][3] BLEEX 45 2 / BLEEX [4] HAL [5][6][7] HAL [8] [ PD-GC) [14] PRMI PD (Fuzzy PD Control with Dynamic Model : …”
Section: Prmi (Exoskeleton In Patternmentioning
confidence: 99%